Stress genesis factors in legal mentality of Ukrainian ethnos in the public discourse - Штепа, О. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article describes the features of stress genesis in legal mentality of the Ukrainian ethnos and destructive influence of injured mentality on the state-building processes in Ukraine are retraced.